The peacock and the sparrow ebook A novel. - Berry, I.S (2023)
THRILLER OF THE YEAR: The Times (London) The Telegraph BEST FIRST NOVEL WINNER: Edgar Awards International Thriller Writers Awards Barry Awards Macavity Awards A BEST BOOK OF THE YEAR: The New Yorker • NPR The Times (London) • The Financial Times • The Guardian • The Telegraph The Diplomatic Courier During the Arab Spring, an American spy's final mission goes dangerously awry in this "crackling debut thriller" ( The New Yorker ) from a former CIA officer heralded as one of the "top spy novelists of the 21st century" ( The Sunday Times , London). Shane Collins, a world-weary CIA spy, is ready to come in from the cold. Stationed in Bahrain off the coast of Saudi Arabia for his final tour, he has little use for his mission—uncovering Iranian support for the insurgency against the monarchy. Then Collins meets Almaisa, a beautiful and enigmatic artist, and his eyes are opened to a side of Bahrain most expats never experience, to questions he never thought to ask. When his trusted informant inside the opposition becomes embroiled in a murder, Collins finds himself drawn deep into the conflict. His budding romance with Almaisa—and his loyalties—are upended; in an instant, he's caught in the crosswinds of a revolution. Drawing on all his skills as a spymaster, he sets out to learn the truth behind the Arab Spring, win Almaisa's love, and uncover the murky border where Bahrain's secrets end and America's begin.